2012
DOI: 10.1111/j.1360-0443.2012.03774.x
|View full text |Cite
|
Sign up to set email alerts
|

Do larger pictorial health warnings diminish the need for plain packaging of cigarettes?

Abstract: Plain packaging probably plays a superior role in undermining brand appeal and purchase intent to increasing health warning size. Policymakers should not rely solely upon large health warnings, which are designed primarily to inform consumers about smoking harms, to also reduce brand appeal: both strategies are likely to be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 32 publications
5
71
2
Order By: Relevance
“…[36][37][38] It is possible that as long as graphic health warnings on cigarette packs appear with powerful branding, brand identity and consumer loyalty might revive at the expense of enduring effects of graphic health warnings on current smokers. 39,40 We found that increased availability of smoking cessation medications was not statistically associated with smoking prevalence. However, smoking cessation products are part of a clinical strategy designed to increase the likelihood of successful cessation among the subset of smokers who are already motivated to make a quitting attempt, but they are not the primary motivator for making the attempt.…”
Section: Discussionmentioning
confidence: 71%
“…[36][37][38] It is possible that as long as graphic health warnings on cigarette packs appear with powerful branding, brand identity and consumer loyalty might revive at the expense of enduring effects of graphic health warnings on current smokers. 39,40 We found that increased availability of smoking cessation medications was not statistically associated with smoking prevalence. However, smoking cessation products are part of a clinical strategy designed to increase the likelihood of successful cessation among the subset of smokers who are already motivated to make a quitting attempt, but they are not the primary motivator for making the attempt.…”
Section: Discussionmentioning
confidence: 71%
“…Evidence from plain packaging simulation studies shows that progressively plainer cigarette packaging, incorporating larger HWLs and fewer branding elements, was perceived as less attractive,19 20 reduced false beliefs about tobacco risk14 17 and was associated with cessation intentions 8 20. Wakefield and colleagues have conducted a number of online simulation experiments, exposing participants to pack conditions which vary by brand, degree of plain packaging19 21 and HWL size 20.…”
Section: Introductionmentioning
confidence: 99%
“…Wakefield and colleagues have conducted a number of online simulation experiments, exposing participants to pack conditions which vary by brand, degree of plain packaging19 21 and HWL size 20. The studies found that packs with progressively fewer branding elements were perceived as less appealing overall,19 larger HWLs combined with plain packs reduced adolescents’ positive ratings of packs,21 and presentation of plain packs compared with branded packs increased participant intentions of not purchasing a pack 20. However, none of these studies examined differences in effects by socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%
“…over time"). 8,9 It took decades of information, education and communication campaigns about the hazards of smoking, as well as the mobilization of key stakeholders, to make plain packaging a priority and garner the multi-sectoral cooperation and political will that eventually led to the measure and to a complementary increase in the price of cigarettes. 10,11 There are also fun ways of nudging individuals into making healthy choices.…”
mentioning
confidence: 99%